Pengaruh Gaya Hidup Dan Servicescape Terhadap Keputusan Pembelian (Studi Pada Semesta Coffee And Space Di Pringsewu) - Bagas Aef Syaifulloh; Aida Sari (GLOBAL SCIENTS PUBLISHER, 2025)
Coffee is an agricultural commodity that plays an important role in the Indonesian economy and culture. This study aims to determine the influence of lifestyle and servicescape on purchasing decisions. This study uses a quantitative approach with a survey method of 114 respondents who are active consumers of Semesta Coffee and Space in Pringsewu, Lampung. Data were collected through questionnaires and processed using SPSS version 24 software. Data analysis used multiple linear regression analysis and hypothesis testing. The results of the analysis indicate that lifestyle and servicescape partially and simultaneously have a significant influence on purchasing decisions. Lifestyle dimensions including Activities, Interests, Opinions (AIO) and servicescape dimensions including ambient conditions, spatial layout and functionality, and signs, symbols, and artifacts are proven to contribute to positive consumer decisions in making purchases. These findings indicate that consumer lifestyle and good physical environment management (servicescape) are important factors in improving purchase decisions in the coffee shop sector